2000
DOI: 10.1034/j.1399-0012.2000.140306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recipient sensitization (peak PRA) on graft outcome in haploidentical living related kidney transplants

Abstract: Sensitization has a significant negative impact on the outcome of haploidentical LRD kidney transplants. Sensitized potential recipients and their potential donors should be aware of this in arriving at informed decision-making for transplantation. These patients may benefit from more sensitive cross-match testing, more intense or more novel immunosuppression, or immunomodulation to modify their immune responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…They also found significantly higher PRA (a PRAϾ50% was present in 10.7% of HCV Ab positive patients versus 1.3% of HCV-negative patients, P ϭ 0.001) and higher retransplantation rates (10.6% versus 4.3%, P ϭ 0.034) in hepatitis C positive patients, but these variables were excluded from their multivariable analysis because they barely missed reaching statistical significance as predictors of graft loss in univariate analysis with reported p-values ranging from 0.056 to 0.12). Of note, however, several studies have reported PRA to be an important predictor of renal graft loss (22)(23)(24). We also found higher PRA and retransplantation to be predictive of renal allograft loss in univariate analysis.…”
Section: Discussionsupporting
confidence: 69%
“…They also found significantly higher PRA (a PRAϾ50% was present in 10.7% of HCV Ab positive patients versus 1.3% of HCV-negative patients, P ϭ 0.001) and higher retransplantation rates (10.6% versus 4.3%, P ϭ 0.034) in hepatitis C positive patients, but these variables were excluded from their multivariable analysis because they barely missed reaching statistical significance as predictors of graft loss in univariate analysis with reported p-values ranging from 0.056 to 0.12). Of note, however, several studies have reported PRA to be an important predictor of renal graft loss (22)(23)(24). We also found higher PRA and retransplantation to be predictive of renal allograft loss in univariate analysis.…”
Section: Discussionsupporting
confidence: 69%
“…1,3,4 Solid-phase single antigen bead assay techniques have facilitated more complete characterization of donor and recipient HLA antigens and allelic variants. 7,9 Therefore, virtual crossmatching has enabled prediction of actual crossmatch results with a high degree of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The Scientific Registry of Transplant Recipients data have shown that time on wait lists is 2 to 3 times longer for patients with elevated PRA levels. 5 In addition, Opelz and associates reported that 1-year and 5-year graft survival for patients with high PRA levels were lower than for patients with low PRA levels.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of lymphocytes giving a positive reaction (cell death) over the total number tested is the PRA of the patient. Sensitized patients who have been exposed to Class I and Class II HLA (human leukocyte antigens) via transfusions, pregnancies and previous transplants are likely to have PRA because they harbor many anti-HLA antibodies that react with larger pool of the donor leukocyte panel [42]. In this assay, it was difficult to determine the exact target of the anti-HLA antibodies since each lymphocytes of the donor would express more than one Class I and II HLA molecules.…”
Section: Patient Assessment: Histocompatibility Testingmentioning
confidence: 99%